Diriger un établissement, entre faire agir les autres et se ménager pour continuer à piloter - Richard Etienne (Éducation et Socialisation)
It was not until the end of the twentieth century that research has begun to focus on the school effect (Grisay, 1990) and, more specifically, the headmaster effect (Gather Thurler, 1998). Headmaster are now being asked to deliver results, which amounts to a radical transformation of their previously control-oriented role. Their actions must be aligned with this mission: to get staff and students to do what they need to do to achieve the goals set by the government. They have to get used to it and endure what it does to himself. Our researches show that in fact he is led to do, therefore to act, with many constraints and to spare himself to serve and survive. What resources must be identified to exercise this new form given to the profession without yielding to the mirage of an idealized management?